Quality of lean body mass and jump capacity in high performance young basketball players lean body mass and jump capacity - Correas-Gómez, L.; Benítez-Flores, S.; Calleja-González, J.; Carnero, E. A. (Journal of Sports Sciences, 2023)
The lean body mass (LBM) components have been suggested as important predictors of anaerobic performance, which is highly involved in basketball. We explored with descriptive cross-sectional design the relationship between anaerobic performance and full molecular and cellular body composition profile in young male basketball players. Twenty-one players (age = 16.8 ± 1.6 years; body mass = 76.3 ± 15.7 kg, height = 189.3 ± 12.6 cm) were recruited, 11 elite and 10 local level. Participants were evaluated on multicomponent body composition [LBM, appendicular lean soft tissue (ALST), bone mineral content (BMC), total body water (TBW), intracellular water (ICW) and extracellular water (ECW)] and field-based anaerobic performance (vertical jump, linear sprint, and handgrip strength). The stepwise regression analyses adjusted for confounders showed significant relationships of whole-body and regional body composition components with handgrip and jump performance (P = 0.03). Prediction models combining body composition variables assessed by bioimpedance analysis (BIA) and double-energy X-ray absorptiometry (DXA) revealed that lean mass and hydration ratios (ICW/ECW and ECW/TBW) were strongly associated with jump performance (CMJ and CMJ25kg), independently of the competition level (P < 0.01). The novel finding in this study was that water quality (ICW/ECW) and water distribution (ECW/TBW, ICW) of total and regional LBM were the main predictors of vertical jump capacity in young basketball players.